2004
DOI: 10.2138/am-2004-11-1205
|View full text |Cite
|
Sign up to set email alerts
|

The most reduced rock from the moon, Apollo 14 basalt 14053: Its unique features and their origin

Abstract: The Apollo 14 high-Al basalt, 14053, is the most reduced lunar rock examined to date. Both fayalite in the mesostasis and spinel minerals have been extensively reduced in the exterior of the rock, whereas the interior contains relatively limited reduction. It is shown that these products are the effects of solar-wind hydrogen that was implanted on the exterior of the "normal" 14053 basalt after it originally crystallized and was weathered to become part of the regolith. Subsequent reheating, probably in an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 16 publications
2
55
1
Order By: Relevance
“…1A). This texture has been described previously and has been suggested to arise from the rock interacting with solarwind-implanted hydrogen at the lunar surface during impactinduced shock metamorphism (41).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…1A). This texture has been described previously and has been suggested to arise from the rock interacting with solarwind-implanted hydrogen at the lunar surface during impactinduced shock metamorphism (41).…”
Section: Resultssupporting
confidence: 62%
“…High-Al basalt 14053 is among the most well-studied samples in the lunar collection. Previous petrographic observations have indicated that sample 14053 is a coarsegrained high-Al basalt (40,41). Previous isotopic studies of the rock have indicated a Rb-Sr crystallization age of 3.92 Ga (e.g., refs.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The low δD values of apatite grains in 14053 can be readily explained by the rocks unique petrologic history, which involved implantation of solar wind protons at the lunar surface followed at some later time by metamorphism in an impact blanket 25 . This would imply that basalt 14053 had a more D-rich signature prior to emplacement on the lunar surface and suggests that this sample should not be used to estimate lunar mantle water contents 9 .…”
mentioning
confidence: 99%